Synthesis of New γ-Lactams with gem-Difluorinated Side Chains - Soulieman, Ali; Gouault, Nicolas; Roisnel, Thierry; Justaud, Frédéric; Boustie, Joël; Grée, René; Hachem, Ali (Synlett, 2019)
A short and efficient approach has been designed for the synthesis of new γ-lactams that feature gem-difluorinated side-chains in position 4. The key steps involve 1,4-addition of nitroalkane anions on electrophilic gem-difluoroalkenes, followed by a cascade nitro reduction–heterocyclization. This flexible strategy also allows easy introduction of substituents in positions 3 or 5.
Keywords: fluorine; gamma lactams; gem-difluoropropargyl; heterocycles; synthesis